BRAZILIAN DISCRIMINALIZATION OF MARIJUANA USERS AND ITS CONSEQUENCES - Madalozo da Rosa, Gilmar; Julia Teixeira Stefanini, Maria (Revista Gênero e Interdisciplinaridade, 2025)
In this article, I discuss the consequences of the Supreme Federal Court’s decision to decriminalize marijuana use. Marijuana has been part of Brazil’s history since the slave trade era and is currently regulated under the Drug Law due to international influences. The recent Supreme Court decision impacts the penal field, driven by existing cool gaps, leading to significant legal and social effects. These include public health issues such as medicinal marijuana use and addiction treatment, as well as social concerns regarding public safety. Finally, there are divergent perspectives on the future: while some sectors are hopeful for complete decriminalization of the plant, others advocate for stricter legislation by the National Congress, such as concerning Law No. 11,343/06.